IL-6 and IL-1β upregulation and tau protein phosphorylation in response to chronic alcohol exposure in the mouse hippocampus. Issue 10 (7th July 2021) - Jiang, Cihao; Zhang, Yi; Tang, Xiaolu; Jing, Chenchen; Qiu, Shasha; Li, Baolin; Li, Yanning
Abstract : Alcoholism and alcohol abuse can lead to memory loss and cognitive dysfunction. The neuroinflammatory response plays an important role in the neurotoxic mechanism of chronic alcohol exposure. Additionally, the phosphorylation status of the tau protein is closely related to neurotoxicity and synaptic function. As inflammatory cytokines have been shown to regulate tau phosphorylation, in the present study, the aim was to determine whether cognitive impairment caused by chronic alcohol exposure is associated with neuroinflammation and tau hyperphosphorylation in the hippocampus. We established a chronic alcohol exposure model of C57BL/6J mice. The Y maze was used to assess the spatial recognition ability of mice, and ELISA was used to detect the levels of inflammatory cytokines IL-1β and IL-6 in the serum. Immunohistochemical and western blot assays were used to assess the expression levels of IL-1β and IL-6, as well as tau protein and its phosphorylation status in the hippocampus. We also analyzed the mRNA and protein expression of the synapse-associated proteins PSD95 and synaptophysin in the hippocampus. Our results showed that chronic alcohol exposure impaired the spatial recognition ability of mice upregulated the expression of IL-1β and IL-6 in the serum and hippocampus and increased the phosphorylation of tau protein in the hippocampus. In addition, chronic alcohol exposure downregulated PSD95 and synaptophysin protein levels. The present results indicate that hippocampal IL-1β, IL-6, and phosphorylated tau proteins may be involved in the neurotoxic mechanism of chronic alcohol exposure by mediating synaptic dysfunction.